2017
DOI: 10.1038/s41598-017-06403-9
|View full text |Cite
|
Sign up to set email alerts
|

Far- and deep-ultraviolet surface plasmon resonance sensors working in aqueous solutions using aluminum thin films

Abstract: Surface plasmon resonance (SPR) sensors detect refractive index changes on metal thin films and are frequently used in aqueous solutions as bio- and chemical-sensors. Recently, we proposed new SPR sensors using aluminum (Al) thin films that work in the far- and deep-ultraviolet (FUV-DUV, 120–300 nm) regions and investigated SPR properties by an attenuated total reflectance (ATR) based spectrometer. The FUV-DUV-SPR sensors are expected to have three advantages compared to visible-SPR sensors: higher sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…When a material has no absorbance, its dielectric constant corresponds to the square of its refractive index n . The changes of the value of ϵ s also have effects on the the dispersion relations; ω in the surface plasmon dispersion relation becomes smaller by increasing the value of ϵ s …”
Section: Al‐spr Properties On a Sapphire Prismmentioning
confidence: 99%
“…When a material has no absorbance, its dielectric constant corresponds to the square of its refractive index n . The changes of the value of ϵ s also have effects on the the dispersion relations; ω in the surface plasmon dispersion relation becomes smaller by increasing the value of ϵ s …”
Section: Al‐spr Properties On a Sapphire Prismmentioning
confidence: 99%
“…The results showed that the refractive indices of carboxyl-MoS 2 in the larger-wavelength region were smaller than those in the short-wavelength region, which resulted in small shifts of the measured SPR angle (whereas a shorter incident wavelength will result in a larger SPR angle). This phenomenon is due to the refractive index (n) and extinction coefficient (k) of the material resulting in different SPP dispersion characteristics of the absorbed wave in different wavelength regions (Tanabe et al, 2017;Kuai et al, 2019). Figure 3D shows the UV-visible absorption spectrum of measured and calculated values for carboxyl-MoS 2 dispersion in water.…”
Section: Analysis Of Coupling Effect Of the Spr Mode In Carboxyl-mos mentioning
confidence: 99%
“…Surface plasmons were also used surface plasmon sensor that detects refractive index changes of the medium in the vicinity of metal. DUV plasmonic sensors using Al and In were developed for sensing molecules with different refractive indices. Since molecules show large refractive indices in the DUV range due to the intrinsic molecular absorption, detection sensitivity is high for DUV plasmon sensors compared to visible ones.…”
Section: Duv Plasmon‐enhanced Molecular Sensing and Imagingmentioning
confidence: 99%